Segregation of Job Duties and Types of Personalityin Responding the Risks - Rentor, Antonius Bimo; Setiawan, Amelia; Lusanjaya, Gery (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2017)
This study aims to analyze the implementation of tasks separation associating with analysis of personality. The object in this study consists of organizational structure and job description of employees in a credit department at one of the banks in Indonesia. This research uses a descriptive method that designed to collect data that describes characteristics of an interesting variable in a certain situation. Data collection consists of literature studies and field research and specific techniques that developed from field research including interviews, questionnaire collection, and field observation. The results show that placement of employees related to functions separation at Relationship Banking Officer unit in credit department does not meet management expectations. This unit has too many employees with various personality types and different respond to risks. Meanwhile, the employee placement at Account Officer unit in credit department has met the management expectation as well as the employee placement at Administration Staff Credit unit. It can be concluded that the procedure of function separation in credit department has been done in accordance with the criteria of the management.